Impact of stress on nutrition in nursing students of a University of the Peruvian Andes - Saldaña-Chafloque, Charles Frank (2023)
Objective: Link stress levels and diet in nursing students from a university in the Peruvian Andes. Methodology: The sampling will be random, the respondents will be randomly selected during the exam and regular education, and the sample will be composed of students of the first, third, fifth and seventh cycle of nursing. Results: Stress, in regular classes are mild (59%), moderate (14%) and normal (27%); and, on examination they are mild (53%), moderate (18%), normal (28%) and severe (1%); Regarding nutritional intake, in regular classes they are inadequate (9%), minimally adequate (49%) and regular (42%); and, in examination they are inadequate (11%), minimally adequate (49%) and regular (40%). 84% of students are women, none smoke, 95% do not drink alcohol. Conclusions: There is a direct relationship with stress levels and nutritional intake in nursing students.